Comparative evaluation of major cropping patterns in coastal saline-alkali lands: Economic, ecological, and social benefits - Hongliang Ma; Dongxu Yang; Maoxing Song; Shangqing Zhang; Chen Wang; Mengying Yang; Tong Li; Zhengyu Yin; Yunting Bian; Cheng Peng; Mochu Wang; Peng Wu; et al. (PLoS ONE, 2026)
Soil salinization constrains agricultural productivity in coastal regions. A two-year field experiment in the coastal saline-alkali farmland of Tangshan, China evaluated three locally adapted cropping patterns: fresh edible pea-rice rotation, rice-crab co-culture, and wheat-rice rotation, with conventional monocropping systems as controls. The fresh edible pea-rice rotation increased net income by 94.78% compared with rice monoculture. The rice-crab co-culture generated the highest economic return, with net income ranging from 24,000–53,400 CNY ha − 1 . The wheat-rice rotation increased net income by 49.8% compared with wheat-maize rotation and by 180.64% compared with rice monoculture. In addition, the cropping patterns showed trends of reduced soil salinity (by 0.13%–0.20% in total soluble salt content) and increased soil organic matter (by 0.20–0.30 percentage points) relative to controls, significantly reduced pesticide inputs by 20%–50% (P < 0.05), and exhibited nitrogen and phosphorus loss reduction rates of approximately 15%–25%. These results demonstrate that optimized cropping patterns can simultaneously enhance economic performance and ecological sustainability in coastal saline-alkali agriculture, with soil quality improvements showing promising trends over the two-year study period.